PENGARUH DITERAPKANNYA PERJANJIAN PENGHINDARAN PAJAK BERGANDA ANTARA INDONESIA-CHINA TERHADAP PERDAGANGAN INTERNASIONAL INDONESIA-CHINA - MAGHFIROH, LAILATUL (Jurnal Akuntansi AKUNESA, 2012)
A tax treaty is an agreement between two countries which regulates the division of tax on income received by residents of one or both parties. Indonesia and China have implemented the double taxation avoidance agreement. The purpose of this research is to investigate the impact of double taxation avoidance agreement by Indonesia and China. To find the difference before and after the implementation of agreements on avoidance of double taxation of international trade between the two countries, it can be done by comparing the average of the second period by using a paired samples t test. The results revealed that application of double taxation avoidance treaty between Indonesia and China is increasing international trade. Key words: international tax law, tax treaty, international trade